Implementation of Quality Control Management for Student Guidance in MAN 1 Parepare - Halik, Abdul; Das, St. Wardah Hanafie (Madania: Jurnal Kajian Keislaman, 2020)
The purpose of this study is to control the quality control of the guidance of the students, to minimize the quality control management barrier in the field of student guidance, and to formulate the applicative concept of the implementation of the quality control management field guidance of students in State Islamic Senior High School (MAN) 1 Parepare. This research method is case study, MAN 1 Parepare as the research object, data collecting technique are observation, interview, document study, triangulation, and Focus Group Discussion (FGD). Data analysis techniques are the identification and reduction of data, analysis, verification and conclusion. As results, MAN 1 Parepare has not applied quality management guidance and counselling learners. Barriers to the implementation of quality control management are limited human resources, insufficient infrastructure, limited budgets, uncompetitive learners, low external support, and limited partnerships. The implementation of quality control management of guidance and counselling field of students in MAN 1 Parepare is to carry out management functions in quality control, beginning with availability of quality standard system, quality procedure, quality audit, and quality control. The institutional requirements of the application of quality control management are the political will of the head of madrasah, the commitment and togetherness of human resources, the fulfilled infrastructure, the adequate budget, and the broad partnership. Tujuan dari penelitian ini adalah untuk mengontrol kualitas bimbingan siswa, meminimalkan hambatan manajemen kontrol kualitas dalam bidang membimbing siswa, dan untuk merumuskan konsep aplikatif dari penerapan bimbingan bidang manajemen kontrol kualitas siswa di Madrasah Aliyah Negeri (MAN) 1 Parepare. Metode penelitian yang digunakan adalah studi kasus, dengan objek penelitian sekolah MAN 1 Parepare, teknik pengumpulan data adalah observasi, wawancara, studi dokumen, triangulasi, dan Focus Group Discussion (FGD). Teknik analisis data adalah identifikasi dan reduksi data, analisis, verifikasi, dan penarikan kesimpulan. Penelitian ini dilaksanakan di MAN 1 Parepare. Sekolah ini belum menerapkan bimbingan manajemen mutu dan konseling peserta didik. Hambatan dalam penerapan manajemen pengendalian kualitas adalah sumber daya manusia yang terbatas, infrastruktur yang tidak memadai, anggaran yang terbatas, pelajar yang tidak kompetitif, dukungan eksternal yang rendah, dan kemitraan yang terbatas. Implementasi manajemen kontrol kualitas bidang bimbingan dan konseling siswa di MAN 1 Parepare adalah untuk melaksanakan fungsi manajemen dalam kontrol kualitas, dimulai dengan ketersediaan sistem standar kualitas, prosedur kualitas, audit kualitas, dan kontrol kualitas. Persyaratan institusional penerapan manajemen kontrol kualitas adalah kemauan politik kepala madrasah, komitmen dan kebersamaan sumber daya manusia, infrastruktur yang terpenuhi, anggaran yang memadai, dan kemitraan luas.